Sun protection counseling at the pharmacy: a german qualitative study on status quo, potential deficits, and sources of information - Diehl, Katharina; Battenberg, Maike Carola; Jansen, Charlotte; Görig, Tatiana (Healthcare, 2023)
The sale of sunscreen products is lucrative for pharmacies, and many people buy sunscreen in pharmacies because they expect to receive good advice on sunscreen use and sun protection. However, little is known about the knowledge level of pharmacists and pharmacy technicians in the field of skin cancer prevention. By conducting a qualitative study in Germany, we aimed to explore what pharmacy personnel know about sun protection and the proper use of sunscreens, where they get their information from, and where they see deficits concerning these topics. We found that there is a need for education regarding the terms skin type and sun protection factor, both of which can be helpful tools when advising customers on sun protection. In addition, participants wished for more independent information from health authorities because sunscreen manufacturing companies, which offer product-specific information, are often the only source of information. Overall, it seems reasonable that pharmacy staff should be educated more about sun protection behavior and the proper use of sunscreen to be able to advise their customers correctly. Our findings offer a starting point for strengthening the role of pharmacies in skin cancer prevention. It seems to make sense to develop and offer tailored handouts for customer counseling. Since sunscreen products are perceived as seasonal products, an educational leaflet can help refresh knowledge about the use of sunscreen and the concepts of skin type and sun protection factor in early summer.
Veröffentlicht: 30. Juni 2023
Gesehen am 17.08.2023